The Effectiveness of Spirituality Therapy on Distress Tolerance and Resilience in Patients with Migraine - Saberi, Azizollah; Kolahdozan, Seyed Ali; Moghimian, Maryam; Jabalameli, Sheida; Mosavizadeh, Rohollah (KMAN Counseling & Psychology Nexus, 2026)
Migraine is a chronic neurological disorder associated with reduced distress tolerance and resilience. The present study aimed to determine the effectiveness of spirituality therapy on distress tolerance and resilience in patients with migraine. In a clinical trial study, patients with migraine attending neurology and counseling clinics in Bam were examined. Through cluster sampling, 44 eligible patients were selected and randomly assigned to intervention and control groups. In addition to pharmacotherapy, the intervention group received 10 sessions of spirituality therapy. The control group received pharmacotherapy. Data were collected using a demographic information form, Gaher’s Distress Tolerance Scale, and Connor’s Resilience Scale, which were completed at pretest, posttest, and one-month follow-up. Data analysis was performed using descriptive and analytical tests in SPSS version 20. The frequency distribution of demographic characteristics was homogeneous in the two groups. Before the intervention, there was no significant difference between the intervention and control groups in the mean scores of the variables. After the intervention, the mean scores of distress tolerance (P = 0.002) and resilience (P < 0.001) in the intervention group showed significant changes compared with both the pre-intervention stage and the control group. The differences in the aforementioned mean scores during the follow-up period compared with before the intervention were significant in the two groups (P = 0.005; P = 0.02). The effect size of the intervention was 0.992 for distress tolerance and 1.59 for resilience, indicating a large effect of spirituality therapy on these variables. The results showed that spirituality therapy, alongside medical treatments, can be effective in the short term in improving distress tolerance and resilience among patients with migraine. The long-term effects of these interventions should be examined so that they can be recommended for managing these psychological states during the course of the disease.